Characteristics, clinical evidence and implementation effects of conditional approvals for drugs in China, a pooled analysis from 2020 to 2023 - Yang, Li; Fan, Shuoxin; Zhang, Jie; Huang, Geyun; Tang, Yaoyang; Xue, Lijia (Frontiers in Pharmacology, 2025)
In late 2019, the conditional approval process for drugs in China transitioned from a pilot project to a formal program. Our study comprehensively analyzed 103 conditional approvals (CAs) authorized by the National Medical Products Administration (NMPA) from 2020 to 2023, specifically focusing on their characteristics, clinical evidence, and implementation effects. It also explored the challenges faced by the CA program in China. The primary findings indicated that nearly 90% of China’s CAs were granted for antineoplastics agents, and there were no reported cases of CAs withdrawn by NMPA from the market. Notably, a substantial disparity existed in the pivotal premarketing and completed/ongoing postmarketing clinical trial features and endpoints. Additionally, CAs which initiated confirmation clinical trials before the CA application submission were more likely to obtain regular approval. The efficacy evidence of CAs supported by single-arm trials demonstrated statistically significant variances in indication and drug types. However, no statistical distinctions were observed in the efficacy evidence of CAs supported by randomized controlled trials (RCTs). CAs have been shown to decrease the development time, review time, and drug lag period, notably compared to non-CAs, and differences exist in the development time, review time, and drug lag period among CAs. Furthermore, numerous unmet clinical needs and the public health emergency of COVID-19 have been partially addressed through CAs. However, the approval procedures, clinical evidence evaluation systems, pharmacovigilance, and requirements for confirmatory trials within China’s CA framework still require further enhancement.